Transcriptome analysis of axolotl oropharyngeal explants during taste bud differentiation stages. (March 2020) - Kohli, Priya; Marazzi, Lauren; Eastman, Deborah
Abstract: The Mexican salamander, Ambystoma mexicanum (Axolotl), is an excellent vertebrate model system to understand development and regeneration. Studies in axolotl embryos have provided important insights into taste bud development. Taste bud specification and determination occur in the oropharyngeal endoderm of axolotl embryos during gastrulation and neurulation, respectively, whereas taste bud innervation and taste cell differentiation occur later in development. Axolotl embryos are amenable to microsurgery, and tissue explants develop readily in vitro. We performed RNA-seq analysis to investigate the differential expression of genes in oropharyngeal explants at several stages of taste cell differentiation. Since the axolotl genome has only recently been sequenced, we used a Trinity pipeline to perform de novo assembly of sequencing reads. Linear models for RNA-seq data were used to identify differentially expressed genes. We found 1234 unique genes differentially expressed during taste cell differentiation stages. We validated four of these genes using RTqPCR and performed GO functional analysis. The differential expression of these genes suggests that they may play a role in taste cell differentiation in axolotls. Highlights: De novo assembly of axolotl embryo explant transcripts provides a source for transcriptome study. RNAseq analysis identifies taste bud development genes in axolotl embryo oropharyngeal explants. At least 1077 genes are differentially expressed in developing axolotl oropharyngeal explants. Cell differentiation genes are differentially expressed in axolotl oropharyngeal explants.